The impact of information technology on human resource management practices from the perspective of education administration employees in Jeddah - Alharbi, Arwa Mohamad; Matoussi, Henda Salem (Journal of Economic, Administrative and Legal Sciences, 2024)
The study aimed to evaluate the impact of information technology on human resources management practices in the Jeddah Education Administration, focusing on technological devices, software, databases, networks and communications, and IT staff. The study employed a descriptive-analytical method and a questionnaire distributed to a sample of 110 individuals from the Jeddah Education Administration. The results showed that the use of information technology has a positive and significant impact on human resources management practices, where technological devices contribute to improving the quality of operations and providing necessary training for employees. The study also indicated the importance of software in facilitating decision-making and its efficient implementation, and the importance of databases in ensuring the accuracy and availability of information. Additionally, networks and communications contribute to facilitating administrative achievements effectively, and IT staff training and feedback are significant (Pearson’s correlation test showed a strong and significant correlation between IT staff and the networks and communications variable, approximately 0.78, and less significant with the database variable, approximately 0.68). The results also show that the use of technological devices (mean: 4.68), software (3.98), databases (4.22), networks and communications (mean: 4.26), and IT staff using technology (4.07) positively and significantly impact the improvement of human resources management practices overall model mean(4.24). The study recommends enhancing the use of information technology in the field of human resources management, improving the quality of training provided to employees, and developing effective mechanisms for collecting and using data to aid decision-making. These recommendations serve as a starting point for future research in the field of information technology and human resources management, particularly in the education sector across various regions of Saudi Arabia.